2018
DOI: 10.1097/meg.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Gut colonization with extended-spectrum β-lactamase-producing Enterobacteriaceae may increase disease activity in biologic-naive outpatients with ulcerative colitis: an interim analysis

Abstract: Gut colonization with ESBL-producing Enterobacteriaceae may increase UC disease activity. Further research is needed to analyze the possible confounding factors that could contribute toward this outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Enterobacteriaceae and Desulfovibrionaceae were abundant in mice with acute colitis, while Rikenellaceae , Akkermansiaceae and Prevotellaceae showed lower abundance. Excessive proliferation of Enterobacteriaceae has been observed in the gut of UC patients [ 32 , 33 ]. Surprisingly, the SCFAs-producing Rikenellaceae , Akkermansiaceae and Prevotellaceae were raised in mice with chronic colitis, which is contradictory to existing reports.…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae and Desulfovibrionaceae were abundant in mice with acute colitis, while Rikenellaceae , Akkermansiaceae and Prevotellaceae showed lower abundance. Excessive proliferation of Enterobacteriaceae has been observed in the gut of UC patients [ 32 , 33 ]. Surprisingly, the SCFAs-producing Rikenellaceae , Akkermansiaceae and Prevotellaceae were raised in mice with chronic colitis, which is contradictory to existing reports.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that patients with IBD had increased abundances of Enterobacteriaceae, including one study reporting Enterobacteriaceae as a dysbiotic signature in patients with IBD in clinical remission. 26,27 In a microbiome study of patients with irritable bowel syndrome (IBS), an increased abundance of Enterobacteriaceae was observed compared to that in the healthy controls. 28 The pathogenicity of Enterobacteriaceae spp.…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae_g were enriched in the altered mucosa group compared to those in the preserved mucosa or control groups and were also found to be a marker of symptomatic non‐remission group. Previous studies showed that patients with IBD had increased abundances of Enterobacteriaceae , including one study reporting Enterobacteriaceae as a dysbiotic signature in patients with IBD in clinical remission 26,27 . In a microbiome study of patients with irritable bowel syndrome (IBS), an increased abundance of Enterobacteriaceae was observed compared to that in the healthy controls 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The improved detection of pathogens has two goals: (1) improving poultry health which safeguards the food supply; and (2) reducing the transmission of antibiotic resistant pathogens and elements. There is a rise in foodborne pathogens containing antibiotic resistance elements that are capable of disseminating to the naïve microbiota ( Nguyen et al, 2016 ; Kassem et al, 2017 ; Vita et al, 2018 ). Therefore, the uncontrolled spread of antibiotic resistant foodborne pathogens increases the risk to the food supply and potentially result in resistant clinical infections ( Economou and Gousia, 2015 ; McCrackin et al, 2015 ; Battersby et al, 2017 ; Kassem et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%